Modernism and the Quadrangular Courtyard: Wellington’s Berhampore Flats, 1938-1940 - Gatley, Julia (Architectural History Aotearoa, 2006)
Wellington’s Berhampore Flats (1938-40) are recognised as being among the first full expressions of modernist architecture in New Zealand. This paper teases out and complicates the accepted interpretation of the Berhampore Flats as being, by New Zealand standards, stylistically advanced, by focusing on one of the ways in which it remained conventional, namely, its retention of a quadrangular courtyard layout. The paper outlines the British medieval, educational, garden city and garden suburb associations of the quadrangular courtyard layout, suggests a possible lineage for Wilson’s use of this layout at Berhampore and considers the implications of his use of the quadrangle in combination with the flat roofs and lack of applied ornament of modernism. The aim of this paper is not to challenge the accepted interpretation of the Berhampore Flats as being stylistically advanced by New Zealand standards, but rather to expand upon and enrich this interpretation by acknowledging that multiple threads and influences can be read into the design.